Valoración del nivel de dependencia en adultos mayores de la comuna Cusin Pamba en San Pablo del Lago - De la Torre Araguillin, Karen Estefany (2024)
Functional independence in Basic Activities of Daily Living (ADLs) is crucial for the quality of life of older adults but is impacted by factors such as aging, chronic diseases, and socio economic conditions. In Ecuador, the aging population presents significant challenges for the healthcare system, particularly in rural communities like Cusin Pamba, where the lack of functional dependence assessment exacerbates the situation. The general objective was to determine the level of dependence among older adults in the Cusin Pamba community of the San Pablo del Lago parish (Otavalo-Ecuador), during June and July 2024. This study employed a non-experimental, cross-sectional design with a quantitative approach and an exploratory descriptive level. A sample of 40 adults aged 65 and over was selected. A structured survey was administered, gathering demographic and health data, and the Katz Index was used to assess functional dependence in ADLs. The results indicated that 80% of the sample maintained full independence in ADLs, reflecting a general state of self-sufficiency. However, the remaining 20% exhibited varying degrees of dependence, particularly in activities requiring fine motor skills such as bathing and dressing. Analysis reveals that functional independence of older adults in Cusin Pamba decreases with age and affects women more than men. Additionally, factors such as marital status, educational level, chronic diseases, and sedentary lifestyle negatively impact functionality.